Thermal and Mechanical Performance of na Optimized Lightweight Masonry Block - Luísa Costa Sousa (2014)
New building materials and modern masonry technologies are emerging in thebuilding marketplace. Masonry, a common component with low maintenance andgood durability is widely used around the world and still remains a main buildingmaterial especially in developing countries. On the other hand the improvement ofthe thermal comfort and energy saving provides a good contribution for thedevelopment of sustainable building. The development of a new block needs to takeinto account the following aspects: material, overall density, thermal and mechanicalrequirements, geometry, topology and laying requirements, production andtechnological constraints. This paper describes the development a new masonrysystem, based on light lightweight concrete units, intended for construction of largesingle leaf external walls with high insulating capacity. A detailed numericalanalysis and optimization has been performed from the thermal point of view. Thissimulation work was followed by a set of experimental tests in order to characterizethe mechanical behaviour of single units and masonry specimens. The averagecompressive strength of the masonry obtained in compression is within the expectedvalues required by the European Standards.